On Line Condition Monitoring of Wind Turbine Generators - Salem, Abdulwahed Almokhtar (Curtin University, 2016)
Condition monitoring has been widely used to detect mechanical and electrical faults of wind turbines in order to avoid catastrophic failures, enhance the reliability and availability of the equipment. This thesis introduces an improved technique to monitor the condition of the wind turbine based on healthy/ faulty operating conditions. A test rig has been developed to analyse various fault levels. Signal processing techniques are compared based on their sensitivity to detect incipient fault conditions.